LEARNER AUTONOMY IN BLENDED LEARNING SPEAKING CLASS - Ida Nahdaleni; Yanuarius Yanu Dharmawan (International Conference on Education and Language (ICEL), 2016)
This research aims to know the condition of learner autonomy in blended learning speaking class and focus on measuring the first level of learner autonomy. The participants of this research were the students who took speaking class. They were the second semester students of English Language Education Study Program of Teacher Training and Education Faculty in Universitas Bandar Lampung. The researcher collected the data from the questionnaire. 12 questions involved in the questionnaire have been proved to have high content validity and high reliability to measure the first of three levels of learner autonomy by Benson (2000). From the data, the researcher found that in blended learning speaking class, the students are in moderate level of autonomy in the context of interdependent level of control over learning management.